2019
DOI: 10.1101/706580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early diverging fungus Mucor circinelloides lacks centromeric histone CENP-A and displays a mosaic of point and regional centromeres

Abstract: 15Centromeres are rapidly evolving across eukaryotes, despite performing a conserved 16 function to ensure high fidelity chromosome segregation. CENP-A chromatin is a hallmark of 17 a functional centromere in most organisms. Due to its critical role in kinetochore architecture, 18 the loss of CENP-A is tolerated in only a few organisms, many of which possess holocentric 19 chromosomes. Here, we characterize the consequence of the loss of CENP-A in the fungal 20 kingdom. Mucor circinelloides, an opportunistic h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…Chromatin immunoprecipitation sequencing (ChIP-seq) of M. circinelloides showed that it has a unique "mosaic" centromere structure in Mucoromycotina, with characteristics from point centromeres (seen in Saccharomyces cerevisiae) and regional centromeres (seen in C. albicans, Candida tropicalis, Magnaporthe oryzae, Schizosaccharomyces pombe, and C. neoformans) (Navarro-Mendoza et al, 2019).…”
Section: Genome Architecture and Structurementioning
confidence: 99%
“…Chromatin immunoprecipitation sequencing (ChIP-seq) of M. circinelloides showed that it has a unique "mosaic" centromere structure in Mucoromycotina, with characteristics from point centromeres (seen in Saccharomyces cerevisiae) and regional centromeres (seen in C. albicans, Candida tropicalis, Magnaporthe oryzae, Schizosaccharomyces pombe, and C. neoformans) (Navarro-Mendoza et al, 2019).…”
Section: Genome Architecture and Structurementioning
confidence: 99%
“…In addition to the highly divergent N-terminal tail, certain changes in the HFD region are declared to be CenH3-specific, so they discriminate CenH3 variants from the canonical H3 and set bioinformatic criteria for identifying putative CenH3 in silico [ 14 ]. Although there have been evidenced species that lack CenH3 [ 6 , 15 , 16 ], CenH3 proteins still represent the most reliable markers of active centromeres. Nevertheless, great interspecies CenH3 varieties, corroborated by extremely divergent underlying DNA sequences, provoke the question of the centromere paradox where the function of the centromere is evolutionarily preserved while its DNA and protein constituents evolve rapidly [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our studies of kinetochore composition of CenH3deficient holocentric lepidopteran species, together with the recent finding of a CenH3-deficient monocentric fungus [28,43] that encodes for other CCAN components, including CENP-T, show that CCAN-based CenH3-independent kinetochore assemblies are considerably widespread in diverse eukaryotes.…”
Section: Discussionmentioning
confidence: 59%
“…Unexpected to its conserved and essential function, CenH3 has been lost in a few select lineages. These include the kinetoplastids [26,27], which have evolved an entirely different kinetochore complex, and an early-diverging fungus with mosaic centromeres characteristic of both regional and point centromeres [28]. In identified the homolog of the a subunit of the ATP synthase (bellwether, GSSPFG00010096001), found previously to localize to kinetochores during Drosophila melanogaster male meiosis [32], indicating that this function might be extended to lepidopteran mitosis.…”
Section: Introductionmentioning
confidence: 93%